2022
DOI: 10.1002/leg3.177
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic rheological properties of sesame protein dispersions

Abstract: Interest in utilizing new sustainable protein sources is increasing, and understanding the rheological behavior of sesame protein can be useful in further application. Small amplitude oscillatory shear measurements of sesame protein dispersions at varying concentrations of 5.0%, 7.5%, and 10.0% were examined at both linear and nonlinear regions. Although the sesame protein dispersions showed pseudoplastic behavior, the shear-thickening effect of sesame proteins at higher concentrations makes it possible to app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Moreover, no differences were observed among all the protein dispersions, and all samples displayed the same slope of the viscosity. The viscosity of the dispersion lowers as the shear rate rises, improving process ability [ 30 ] These results were in agreement with those obtained by Rafe et al [ 31 ] who found that the viscosity was decreased linearly with frequency demonstrating the shear thinning phenomenon.
Fig.
…”
Section: Resultssupporting
confidence: 88%
“…Moreover, no differences were observed among all the protein dispersions, and all samples displayed the same slope of the viscosity. The viscosity of the dispersion lowers as the shear rate rises, improving process ability [ 30 ] These results were in agreement with those obtained by Rafe et al [ 31 ] who found that the viscosity was decreased linearly with frequency demonstrating the shear thinning phenomenon.
Fig.
…”
Section: Resultssupporting
confidence: 88%